What Factors Influence the Entrepreneurial Behavior and Performance of MSMEs Survivors of Covid-19? - Meicy Augustine Lembono; Chrisanty Victoria Layman (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The objective of this research is to analyze the impact of individual factors, environmental factors, and entrepreneurial behavior on the performance of MSMEs post the height of the Covid-19 pandemic.Methodology: This study uses a quantitative approach and the data was obtained by a questionnaire with 170 respondents from Jakarta who run micro, small, and medium enterprise (MSME) and applies digitalization in their business process. Data were processed using the SEM-PLS program.Finding: The result shows that individual factors influence entrepreneurial behavior. In addition, environmental factors influence individual factors. However, individual factors don’t significantly influence firm performance. Meanwhile individual and environmental factor mediates entrepreneurial behavior’s positive influence on firm performance. Conclusion: This study concludes that many, not only internal but external factors play a key role in how certain MSMEs can cope and survive during the Covid-19 pandemic. This study also contributes to showcasing some of the responses to government involvement and digitalization coupled with the MSMEs’ entrepreneurial behavior that can influence their performances.